The informal sector in developing countries: Output, assets and employment - Sangeeta Pratap; Erwan Quintin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This study documents four key facts about informal economic activities: (1) the size of the informal sector varies greatly across nations; (2) this size is strongly correlated with economic development, the tax burden, and the rule of law; (3) the informal sector emphasizes small-scale, self-financed and unskilled labour intensive economic activities; and (4), while financial markets are generally segmented along formal/informal lines in developing nations there is no compelling evidence that this is true for labour markets. We review the existing theoretical literature on the informal sector and describe a simple model with a tradeoff between tax evasion and access to formal sources of outside finance which is consistent with much of the existing evidence. Finally, the study discusses the challenges associated with measuring informal sector assets.
Keywords: O17; L23; E24; 330; segmented labour markets; informal sector; Informeller Sektor; Theorie; Entwicklungsländer